(untitled) (Texas Journal of Medical Science, 2023)
The article describes experimentally induced hypothyroidism and the changes in the face-jaw system as a result of its development. In particular, the morphological changes in the teeth are studied. The article provides a lot of information about the morphological changes in the teeth as a result of the spread and development of hypothyroidism in many countries around the world, and their negative consequences